The Influence of Digital Literacy, Fintech Usage, and Business Innovation on the Financial Reporting Quality of MSMEs through Accounting Process Efficiency as a Mediating Variable - Tanjung, Putri Renalita Sutra; Wahyudi, Sely Megawati; Chairunesia, Wieta; Oktasari, Dian Primanita (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose: This study aims to examine the influence of digital literacy, fintech usage, and business innovation on the financial reporting quality of MSMEs in Bandung City, with accounting process efficiency as a mediating variable. Method: A quantitative approach was employed using a cross-sectional survey method involving 100 MSMEs. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships between variables. Findings: The results show that digital literacy and business innovation have a positive and significant effect on financial reporting quality, both directly and through accounting process efficiency. Conversely, fintech usage does not show a significant impact. Accounting process efficiency is proven to be an important mediator that strengthens the influence of digital literacy and innovation on financial reporting. Implications: Theoretically, this study reinforces the TAM, RBV, and Information Quality Theory models by highlighting the mediating role of accounting process efficiency. Practically, the findings emphasize the need for digital literacy training integrated with accounting practices and the development of fintech systems that are compatible with MSME bookkeeping.